Pembuatan Media Pembelajaran dan Pengujian Motor Starting System (207-1556 CW) - Ari, A. Ariputra; Pitriadi, Peri; Halim, Abdul; Maulana Ilmunandar, Alief; Ishak, Ishak (Jurnal Teknik Mesin Sinergi, 2024)
Starting motors have an important role in running heavy equipment engines, accuracy in testing starting motor components is a very important factor. Practical learning using starting motor testing media is used to practice starting motor assembly and disassembly. The problems experienced by students in this course are limited practical equipment and lack of student skills regarding assembly and disassembly of motor starting systems. The aim of this research is to create learning media for testing motor starting systems and create a motor starting system testing guide so that it can be used as a practical tool in heavy equipment maintenance workshops. Experimental methods and work processes include: 1) determining materials, 2) designing the frame, 3) working on the frame, 4) making disassembly guides, testing, and starting motor assembly. The results of this research are that the learning media is equipped with the main components of the motor starting system, measurements that display motor starting system testing information, namely: the process of disassembly, testing and assembly of the starting motor, so that this learning media can increase students' understanding of the function and operation of the starting motor. system, as well as providing practical experience in testing and understanding related components.